Reconstruction of anthropogenic 129I temporal variation in the Japan Sea using a coral core sample. (November 2018) - Sakaguchi, Aya; Inaba, Rui; Sasa, Kimikazu; Matsunaka, Tetsuya; Hosoya, Seiji; Takahashi, Tsutomu; Honda, Maki; Yamano, Hiroya; Sasaki, Keiichi; Yamasaki, Shinya; Watanabe, Tsuyoshi; Sueki, Keisuke
Abstract: The anthropogenic long-lived radionuclide 129 I is receiving increased attraction as a new oceanic tracer in addition to usage as a fingerprint of radionuclide contamination of the marine environment. To demonstrate the robustness of 129 I as an oceanic tracer in the Northwest Pacific area, specifically in the Japan Sea, the input history of 129 I to surface seawater was reconstructed using a hermatypic coral core sample from Iki Island in the Tsushima strait. Iodine isotopes in each annual band were measured using AMS and ICP-MS after appropriate pre-treatments of small amounts of coral powder. The 129 I/ 127 I ratios in the 1940s were almost at background levels (<1 × 10 −11 ) and increased abruptly in the early 1950s. Thereafter, the ratios continuously increased with some fluctuations; the maximum ratio, 7.13 ± 0.72 × 10 −11, being found in the late 1990s. After that period, the ratios remained nearly constant until the present time (2011). The 129 I originated mainly from the nuclear weapons testings of the 1950s and the early 1960s, and from airborne releasing by nuclear reprocessing facilities. The dataset obtained here was used to construct a simple model to estimate the diffusion coefficient of 129 I in the Japan Sea. The 129 I/ 236 U ratios over the observation period were also reconstructed to help constraining sources of 129 I to the marine environment. Based on the results, the 129 I/ 236 U ratio obtained here could be an endmember of the water mass in the Kuroshio Current area of the Northwest Pacific Ocean. Highlights: The temporal distribution of 129 I in the Japan Sea was reconstructed. The 129 I/ 127 I ratios increased abruptly in the early 1950s. The 129 I originated mainly from the nuclear weapons testings and nuclear reprocessing plants. The 129 I/ 236 U ratio can be used as robust oceanic circulation and mixing tracers.